Isolation and characterization of microsatellite loci in the endangered perennial Eleocharis parvula (Cyperaceae), emerging in the 2011 tsunami inundation areas. Issue 2 (7th June 2016) - Kimura, Takuma; Yamazaki, Shohei; Uno, Kunihiko; Yamada, Takayuki; Maki, Masayuki
Abstract: Using 454 pyrosequencing, we designed primers for 12 microsatellite loci in the endangered perennial herb Eleocharis parvula, which has established many new populations in areas disturbed by the huge tsunami following the Great East Japan Earthquake in 2011. Polymorphism of these 12 loci was assessed in 25 individuals from two newly established populations in the tsunami disaster area. The number of alleles ranged from two to five, and the ranges of observed and expected heterozygosity were 0.167–0.833 and 0.219–0.727, respectively. These loci were not linked to each other and had no null alleles. These markers will be useful in studies of the genetic diversity, population dynamics and conservation of E. parvula . Abstract : We designed primers for 12 microsatellite loci in the endangered perennial herb Eleocharis parvula, which has established many new populations in areas disturbed by the huge tsunami following the Great East Japan Earthquake in 2011. These markers will be useful in studies of the genetic diversity, population dynamics, and conservation of E. parvula .